Modeling of the suitables areas of adaptation of tejocote (Crataegus mexicana DC.) by global climatic change. - Núñez-Colín, Carlos Alberto (2012)
The objective of this research was to determine the possible displacement of Crataegus mexicana DC from its current adaptation zones due to the influence of climate change. Two models of suitable growing areas were constructed, one using current climate data and the second using data of the CCM3 model, which predicted the possible climate change to 2050. The model with current climatic data showed that the current growing areas of central Mexico have high to excellent growing conditions, as similar areas of the Transmexican Volcanic Axis, Mexican Plateau, Sierra Madre Oriental, and Sierra Madre del Sur. This model also showed limited adaptation areas on the northeast, northwest and south of the country. In contrast, with the CCM3 model the Transmexican Volcanic Axis, including the current growing areas, improved the conditions from very high to excellent, and improved conditions for cultivation in this and other regions of the country. Therefore, the tejocote will be positively affected by the change in temperature and rainfall to 2050, which could result in an increase in the area dedicated to this crop.